Bus accident record;The return of accident proneness - af Wåhlberg, Anders E.; Dorn, Lisa (Taylor & Francis, 2009)
One of the assumptions of the theory of accident proneness is that drivers’ accident liability is stable over time which was tested in the present paper. Previous investigations of this problem (or rather the conclusions) were found to be deficient, because they did not take into account the statistical problem of low variance in the accident variable. However, by correlating the between time periods association coefficient and the mean number of accidents across several samples, this problem can be overcome. Therefore, the stability of accident record over time was investigated in five samples of British bus drivers. It was found that the size of the correlations between time periods increased with the increase in mean accident frequency. Furthermore, this increase could be described by a linear regression line, which fit the various points extremely well. Also, the size of correlations of At fault accidents increased faster with the mean than did All accidents, although the latter had a higher initial value. It was therefore concluded, in contrast to previous authors, that the accident record of drivers is quite stable over time, and that the very low correlations which have often been found were due to the samples and methods used (low-risk drivers and short time periods equalling low crash means), and not of any inherent instability in drivers’ behaviour and/or accident record. It was also concluded that only culpable accidents should be used for this type of calculation. No evidence was found for a decrease in correlation size between single years' accidents when time periods between the years were lengthened, i.e. accidents in one year predicted accidents in several other years equally well. However, the period used was rather short. The results are discussed with reference to training intervention for accident–involved drivers, especially for organizations with major fleets such as bus comp
Keywords: accident proneness, bus driver, crash, reliability, stability, accident record